SiW ECAL for future e+e− collider. (6th July 2017) - Balagura, V.; Bilokin, S.; Bonis, J.; Boudry, V.; Brient, J.-C.; Callier, S.; Cheng, T.; Cornat, R.; Taille, C. De La; Doan, T.H.; Frotin, M.; Gastaldi, F.; et al.
Abstract: Calorimeters with silicon detectors have many unique features and are proposed for several world-leading experiments. We discuss the tests of the first three 18×18 cm 2 layers segmented into 1024 pixels of the technological prototype of the silicon-tungsten electromagnetic calorimeter for a future e + e − collider. The tests have beem performed in November 2015 at CERN SPS beam line.